Fluoro‐2‐deoxy‐d‐glucose positron emission tomography/computed tomography for the detection of proximal synchronous lesions in patients with obstructive colorectal cancer. Issue 2 (February 2017) - Kim, Wan Soo; Lee, Hyo Sang; Lee, Jeong‐Mi; Kwak, Min Seob; Hwang, Sung Wook; Park, Sang Hyoung; Yang, Dong‐Hoon; Kim, Kyung‐Jo; Myung, Seung‐Jae; Yang, Suk‐Kyun; Byeon, Jeong‐Sik
Abstract: Background and Aim: We aimed to investigate the ability of fluoro‐2‐deoxy‐d ‐glucose (FDG) positron emission tomography (PET)/computed tomography (CT) to detect synchronous neoplasms, specifically obstructive colorectal cancer (CRC) and CRC in the proximal colon and to suggest a management strategy based on FDG PET/CT findings. Methods: From the CRC surgery database of our institution, 518 patients with obstructive CRC whose proximal colon could not be examined by colonoscopy and who underwent preoperative FDG PET/CT were eligible for this study. Of these, final analyses were performed in 345 patients who had reference standards for the proximal colon, which were a surgical colectomy specimen and/or postsurgical colonoscopy. The per‐patient and per‐lesion performances of FDG PET/CT for synchronous CRC diagnosis were determined. Results: Of 345 patients, 14 (4.1%) had 14 proximal synchronous CRCs. Thirty‐four patients showed 39 areas of abnormal FDG uptake on PET/CT in the colon proximal to the obstructive CRC. PET/CT detected all of the 14 proximal synchronous CRCs. The per‐patient PET/CT sensitivity, specificity, positive predictive value, and negative predictive value for proximal synchronous CRC were 100%, 93.9%, 41.2%, and 100%, respectively. Per‐lesion values were 100%, 92.6%, 35.9%, and 100%, respectively. The per‐lesion sensitivity and negative predictive value of PET/CT for advanced adenoma were 45.5% and 92.7%, respectively. Conclusions: The FDG PET/CT shows a high sensitivity and negative predictive value for the detection of proximal synchronous CRC in patients with obstructive CRC, enabling negative findings in the proximal colon on PET/CT to definitively exclude proximal synchronous CRC. Preoperative PET/CT recommended to determine the proper surgical plan in patients with obstructive CRC.